The Village in Al-Ashmawi’s Diwan of (The Basil Vendor) - Elgheity, Mrwa Mokhtar (Journal of Arabic Language Sciences and Literature, 2023)
The study sought to trace village landmarks in Abdurrahman Al-Ashmawi’s Diwan of (The Basil Vendor) and aimed to learn about the village’s features and its relationship with the poet’s social life, its impact on himself and his conscience. It assumed a close association between the poet and his village (Araa). The study used the descriptive method; to open up to a limited cultural vision of the village that reflected the poet’s experience. The researcher attempted in the first section to identify the village’s features and their impact on the affiliation of the poet, and in the second section she came to know about the social life of the village, its aesthetic and semantic role, while in the third section she dealt with the impact of the village on the poet’s life. The study has come up with some results, including the poet’s preference for the village over the city, and the psychological attachment to it. The village has emerged as an affectionate and attractive place contrary to the city, which was a source of concern and insomnia. The research also recommended studying Ashmawy’s literary production to enrich modern critical studies of contemporary Saudi poetry.